Dreptul achiziției publice ca instituție sau ca sub-ramură a dreptului administrativ [Articol] - Postolachi, Oxana; Cîrnaţ, Teodor (My University, 2023)
The public procurement mechanism ensures the transparent and fair procurement of goods, the execution of some works or the provision of services for public needs either at the central or local level. Obtaining an efficient and credible public procurement system is one of the important elements in the development of quality public services. State regulation of the field of procurement involves the activity of competent public authorities, in executive terms, regarding the rules, standards and requirements according to which public procurement procedures are carried out. As the main competent authority in the field of public procurement, there is the Public Procurement Agency (AAP), which is an administrative authority subordinate to the Ministry of Finance, established for the purpose of supervision, ex-post control and interbranch coordination in the field of public procurement. Public procurement law is subordinated to administrative law. Our research involves framing public procurement law as an institution or as a sub-branch of administrative law, depending on its evolution over time.
PUBLIC PROCUREMENT LAW AS AN INSTITUTION OR AS A SUBBRANCH OF ADMINISTRATIVE LAW
Keywords: achiziții publice; procurement